CISA Certified Information Systems Auditor : study guide - Cannon, David L. 1962-; O'Hara, Brian T.; Keele, Allen (Sybex, 2016)
The ultimate CISA prep guide, with practice exams Sybex's CISA: Certified Information Systems Auditor Study Guide, Fourth Edition is the newest edition of industry-leading study guide for the Certified Information System Auditor exam, fully updated to align with the latest ISACA standards and changes in IS auditing.